2013
DOI: 10.3390/ijerph10083325
|View full text |Cite
|
Sign up to set email alerts
|

A Food Retail-Based Intervention on Food Security and Consumption

Abstract: The effect of the built environment on diet (and ensuing health outcomes) is less understood than the effect of diet on obesity. Natural experiments are increasingly advocated in place of cross-sectional studies unable to suggest causality. The central research question of this paper, therefore, asks whether a neighborhood-level food retail intervention will affect dietary habits or food security. The intervention did not have a significant impact on fruit and vegetable consumption, and the intervention popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
126
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(129 citation statements)
references
References 45 publications
3
126
0
Order By: Relevance
“…In contrast, other studies maintain that there is no causal linkage between access to food markets and dietary diversity. A study in Michigan, USA, for example, found that physical distance to food outlets providing healthy food did not significantly influence fruit and vegetable consumption [5]. Another study suggests that it is the price of food in supermarkets, rather than the physical distance to market, that most influences the consumption of fruits and vegetables [6].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other studies maintain that there is no causal linkage between access to food markets and dietary diversity. A study in Michigan, USA, for example, found that physical distance to food outlets providing healthy food did not significantly influence fruit and vegetable consumption [5]. Another study suggests that it is the price of food in supermarkets, rather than the physical distance to market, that most influences the consumption of fruits and vegetables [6].…”
Section: Introductionmentioning
confidence: 99%
“…at the same time, single interventions such as a new grocery store can make for rather draconian solutions to the complexity of poor food access, which is shaped by both the supply-side factors noted above and socioeconomic conditions of particular places. Nevertheless, they are currently the most studied food desert interventions, and the results here are similarly mixed (cf., Wrigley, 2002;Cummins et al, 2005Cummins et al, , 2008Sadler, Gilliland, & arku, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, environmental ecology is instrumental in physical activity-related behaviors, eating patterns, and access to nutritious foods. Yet, disparities exist within physical environments based on factors such as neighborhood socioeconomic status [20,21].…”
Section: Environmental Justicementioning
confidence: 99%
“…In this sense, food security interventions that rely on the establishment of grocery stores may not be operative in food system change. Similarly, emergency food programs targeting diverse populations may not be effective in decreasing food insecurity if service providers fail to offer culturally-appropriate food and support services when distributing food [20,33]. Food security initiatives, like alternative food movements, can be seen as seeking a re-distribution of benefits within dominant, oppressive food systems to combat hunger and promote wholesome, nutritious ways of eating within marginalized communities.…”
Section: Food Securitymentioning
confidence: 99%
See 1 more Smart Citation